The curative effect analysis of simultaneous U-VATS for bilateral multiple primary early-stage lung cancers - Shi, Miao; Wang, Long-fei; Zhang, Xue-chi; Tang, Li-wei; Zheng, Lei; Hu, Wen-tao; Liang, Zhi-gang (Frontiers in Oncology, 2025)
BackgroundThe incidence of multiple primary lung cancers (MPLCs) has been on the rise over the past decade, yet optimal surgical strategies remain debated. This study compared perioperative outcomes and long-term quality of life (QoL) between simultaneous and staged uniportal video-assisted thoracoscopic surgery (U-VATS) for bilateral early-stage MPLC.MethodsA retrospective cohort analyzed 69 patients undergoing simultaneous (n=28) or staged (n=41) U-VATS between March 2021 and December 2023. A comparative statistical analysis was conducted to assess perioperative efficacy and long-term QoL between simultaneous versus staged U-VATS in patients with bilateral synchronous MPLCs.ResultsThe simultaneous group exhibited smaller tumors (P=0.002) and included more smokers (P=0.019). Compared to staged surgery, simultaneous U-VATS resulted in a shorter hospital stay (8 vs. 14 days, P<0.001), reduced non-steroidal drug use (240 vs. 440 mg, P<0.001), and lower costs (CNY 41218.11 vs. CNY 68041.55, P<0.001), with comparable operative times (P=0.193). Pulmonary infections were less common following simultaneous surgery (3.6% vs. 24.4%, P=0.045). No 30-day mortality occurred. Longitudinal QoL assessment using a standardized 8-item symptom scale (cough, polypnea, pain, fatigue, sweating, insomnia, constipation, throat irritation) identified significant advantages for simultaneous surgery in polypnea (P=0.015) and pain control (P=0.013), whereas remaining symptoms showed comparable trajectories (all P>0.05).ConclusionSimultaneous U-VATS may be a safe, cost-effective option for early-stage MPLC, particularly in patients with smaller tumors. Larger multicenter studies are warranted to validate these findings.